Morphological variation in nanche fruits (Byrsonima crassifolia), in the dry tropic: Morfología en frutos de nanche - Maldonado Peralta, Maria de los Angeles; Rojas García, Adelaido Rafael; Maldonado Peralta, Ramiro; Salinas Vargas, Delfina; Wilson García, Claudia Yanet; Sabino López, Juan Elías (Ecosistemas y Recursos Agropecuarios, 2021)
Nanche is a species that develops in tropical conditions, with marginal soils. The research was proposed with the objective of evaluating the morphological variation of wild nanche fruits. For the development of the investigation, the surroundings of the municipality of Cuajinicuilapa, Guerrero, Mexico; where 200 trees were located in fruit production, these were collected from the ground and transferred to the Laboratory of the Faculty of Veterinary Medicine and Zootechnics No. 2. They were selected and according to their characteristics were gathered, leaving 16 accessions, to which The weight of fruit, pulp and seed, polar and equatorial diameter of fruit, seed and embryos, fruit shape, number of embryos and color were determined. The data were evaluated with measures of central tendency of the SAS. It was found that wild nanche fruits weigh between 0.78 and 5.13 g, are of commercial quality, some accessions have high pulp content in relation to the seed; Furthermore, the shape of the fruit determines that of the seed, as it was in accessions 4, 5, 6 and 8, but the size depends on the phenotype. The number of embryos does not affect the size of the seed or the fruit, because large seeds are not necessarily large fruits. Accessions 3 and 12 are recommended for propagation, consumption and export. The morphological variation found depends on the phenotypes and the environmental conditions in which the genotype develops.